Guide for the development of bicycle facilities, 2012 (American Association of State Highway and Transportation Officials, 2012)
"This guide provides information on how to accommodate bicycle travel and operations in most riding environments. It is intended to present sound guidelines that result in facilities that meet the needs of bicyclists and other highway users. Sufficient flexibility is permitted to encourage designs that are sensitive to local context and incorporate the needs of bicyclists, pedestrians, and motorists."--Publisher's website.
'Publication Code: GBF-4."
Updates the previous edition published in 1999.
Keywords: Bicycle trails -- Handbooks, manuals, etc.; Bicycle trails -- Design and construction -- Handbooks, manuals, etc.; Roads -- Design and construction -- Handbooks, manuals, etc.; elektronické knihy; electronic books